Awareness of Nurse Midwives’ toward Post-miscarriage Care at Bint Al-Huda Hospital in Al-Nasiriya City - Hiba Jasim Hammood1 , Sarah Talib Kadhim2 , Oday Faris Washeel3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective of Study: To assessment of nurse-midwives’ knowledge and performance concerning with post abortion Care. Methodology: A cross sectional descriptive analysis of (50) nurse midwives of this category of maternity nurse midwives was conducted in separate units of the Bint Al-Huda hospital between 19 January 2020 and 30 April 2020. The questionnaire’s validity and reliability was calculated through a pilot test. Due to the condition in the nation and the governorate, the emergence of the Corona epidemic and the implementation of curfews, the questionnaire was submitted electronically and the questionnaire was completed by the nurses and midwives, data was processed using the SPSS edition (20). Results: The test showed that 22% of the test sampler replied correctly to Encourage the client to clear the toilet, 44% replied correctly to isolation of infected patients, 20% of the study sample responded correctly to the importance of hand washing, 35% responded correctly to Asses vaginal bleeding, 25% of the research sample responded correctly in, In terms of emotional assistance, 30 percent responded correctly,19 percent of the research sample replied with right Test vital signs. 38 percent of them correctly replied with regard to the patient’s medical profile, 40 percent of the test group correctly replied with regard to Perineum care.